The potential of the addition of Secang wood extract on physico-chemical properties, antioxidant and antibacterial activities of goat-milk kefir as a functional food product - Rizka Mulyani; Nurliyani Nurliyani; Indratiningsih Indratiningsih; Prakoso Adi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
This study aimed to improve the functional quality of goat-milk kefir by adding secang wood extract. The initial stage of the research was the extraction of secang wood using distilled water. Kefir is made by mixing secang wood extract and pasteurized goat milk with 5% kefir grains, then incubated at 25ÌŠC for 20 hours. Goat-milk kefir was then tested for physicochemical quality (i.e., total solids, water content, pH value, acidity value, viscosity, and alcohol content), microbiological quality (i.e., total lactic acid bacteria (LAB) and total yeast), organoleptic properties, antimicrobial activity against Escherichia coli and Staphylococcus aureus, and antioxidant activity. The results showed that the physicochemical quality of kefir with the addition of secang wood extract had an effect (p<0.05) on total solids, water content, pH value, acidity value, and viscosity. The results showed that the addition of secang wood extract 8% to goat-milk kefir has an antioxidant activity of 12.18% and an antibacterial activity by inhibiting Escherichia coli and Staphylococcus aureus 24.81mm and 18.95mm, respectively. These findings confirmed that goat-milk kefir, with the addition of secang wood extract, has the potential as a functional food.